Evaluation of the Validity and Psychometric Properties of the Persian Version of the Brain Fog Questionnaire - Mosayebi, Mahshad; Khoshlahjeh Sedegh, Anis (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The primary aim of this study was to examine the psychometric properties (validity and reliability) of the Persian version of the Brain Fog Scale in an Iranian student population.Methods and Materials: This research was a cross sectional, descriptive analytical study. A sample of 300 students from Islamic Azad University, Qom Branch, was selected using convenience sampling. In addition to the Brain Fog Scale (BFS), participants completed measures for convergent validity (Cognitive Load Questionnaire and General Health Status) and divergent validity (Meal Frequency and Physical Activity Questionnaire). Data were analyzed using SPSS (version 27) and AMOS (version 24).Findings: Confirmatory factor analysis supported the three factor structure of the scale (mental fatigue, reduced cognitive sharpness, and confusion) with very good fit indices (CFI = 0.96, RMSEA = 0.045, χ²/df = 2.3). The instrument demonstrated excellent internal consistency with Cronbach’s alpha = 0.935 for the total scale and 0.785 to 0.876 for the subscales. Test retest reliability was confirmed with a correlation coefficient of 0.942, indicating high temporal stability. A significant positive correlation between brain fog scores and cognitive load (r = 0.284) and a significant negative correlation with general health status (r = -0.202) supported the instrument’s convergent validity. The questionnaire also successfully discriminated scores across educational levels, with doctoral students reporting higher brain fog scores than undergraduate and master’s students.Conclusion: Overall, the findings indicate that the Persian version of the Brain Fog Scale (BFS) is a valid, reliable, and culturally appropriate tool for assessing brain fog symptoms in the Iranian student population. This study confirms the scale’s three factor structure and supports its use in future research and clinical assessments.